Construction of a mathematical model of the film absorber for sulfating two-component mixtures of organic substances - Dzevochko, O.; Podustov, M.; Dzevochko, A.; Panasenko, V. (PC Technology Center, 2021)
The processes that occur in film absorbers during the sulfation of two-component mixtures of organic substances are quite complex and require mathematical modeling. This paper reports the construction of a mathematical model that makes it possible to adequately describe the process of sulfation involving gaseous sulfur trioxide in the production of surfactants. Based on the model, it became possible to investigate this process for higher alcohols of fractions C₁₂–C₁₄ and monoethanolamides of higher fatty acids of coconut oil. The data are given on the comparison of mathematical modeling results based on the mathematical model built with known experimental data and results of alternative mathematical modeling for different ratios of the length of the reaction pipe to its diameter (l/d). It is shown that the error in comparing the experimental data was 4.8–9.6 % at l l/d=29; 1.1–8.7 % at l/d=70; 3.9–12.3 % at l/d=144. The error in comparing known results of alternative mathematical modeling was, respectively, 6.3–7.2 %, 0.1–6.5 %, 0–1.0 %. These results were obtained for the molar ratio in the range of 1.0–1.15 and the SO3 concentration in the stream of 4.0–6.0 %. Such findings suggest that the established dependences of the basic parameters for the sulfation process are adequate in terms of the absorber length and its radial direction. Therefore, the mathematical model built does hold within the considered ranges of input variables. Consequently, it could be used in the theoretical study of the process of sulfation of two-component mixtures of organic substances by gaseous sulfur trioxide in a film absorber with a downward flow of phases. The results obtained could be used in practice, in particular in the manufacture of high-quality products for the cosmetic industry.
Keywords: mathematical model; process of sulfation; film absorber; surfactant; two-component mixture